Measuring the Effects of Entrepreneurial Orientation on Social Media Adoption and SME’s Performance in Kathmandu Valley: Evidence from Structural Equation Modeling Using Smart PLS 4.0 - Maharjan, Rubi; Danuwar, Ranjana Kumari; Kayestha, Mijala; Dhakal, Ajaya; Baral, Deep Kumar; Rajopadhyaya, Alish; Koirala, Amita; Timalsina, Dhurba Prasad (Economic Journal of Development Issues, 2024)
Social media platforms have become crucial for Small and Medium Enterprises (SMEs) to enhance their online presence and engagement in the contemporary digital media landscape. The study highlights the significance of entrepreneurial orientation in utilizing social media for SME growth and performance, especially in the face of challenges like digital literacy and infrastructure gaps. Furthermore, the study outlines its structure and aims to establish a link between entrepreneurial orientation, social media adoption, and SME performance, offering insights to guide future initiatives. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was utilized to test four hypotheses among 280 respondents to analyze the connections and causal relationships between the effect of entrepreneurial orientation on social media adoption and SME performance. The findings reveal that a lack of knowledge and skills, limited resources for investing in social media, and privacy and security concerns are significant challenges to adopting social media. SEM results indicate a significant relationship between entrepreneurial orientation (β= 0.264, P